Relasi Sistem Kekerabatan pada Arsitektur Tradisional di Desa Prapau Semende Sumatra Selatan - Syahfira Dwinda; Christina Gantini; Johannes Adiyanto (Universitas Muhammadiyah Palembang, 2024)
Traditional architecture is a cultural heritage resulting from the lives of traditional communities, encompassing both art and architectural knowledge. Similar to traditional architecture in many other regions of the Indonesian archipelago, traditional Semende architecture represents cultural heritage with variations in function, ornamentation, and form, often referred to as